Swimming training prevents metabolic imprinting induced by hypernutrition during lactation. Issue 1 (February 2015) - Fischer, Stefani Valeria; Capriglioni Cancian, Cláudia Regina; Montes, Elisangela Gueiber; de Carvalho Leite, Nayara; Grassiolli, Sabrina
Summary: Background & aims: Reduction in litter size during lactation induces hypernutrition of the offspring culminating with altered metabolic programming during adult life. Overnourished rats present alterations in the endocrine pancreas and major predisposition to the development of type 2 diabetes. Our study evaluated the impact of swimming training on insulin secretion control in overnourished rats. Methods: At postnatal day 3 male rat pup litters were redistributed randomly into Small Litters (SL, 3 pups) or Normal Litters (NL, 9 pups) to induce early overfeeding during lactation. Both groups were subjected to swimming training (3 times/week/30 min) post-weaning (21 days) for 72 days. At 92 days of life pancreatic islets were isolated using collagenase technique and incubated with glucose in the presence or absence of acetylcholine (Ach, 0.1–1000 μM) or glucagon-like peptide 1 (GLP1, 10 nM). Adipose tissue depots (white and brown) and endocrine pancreas samples were examined by histological analysis. Food intake and body weight were measured. Blood biochemical parameters were also evaluated. Results: Swimming training prevented metabolic program alteration by hypernutrition during lactation. Exercise reduced obesity and hyperglycemia in overnourished rats. Pancreatic islets isolated from overnourished rats showed a reduction in glucose-induced insulin secretion and cholinergic responses while the insulinotropic action of GLP1 was increased. Physical training effectively restored glucose-induced insulin secretion and GLP1-stimulated action in pancreatic islets from overnourished rats. However, swimming training did not correct the weak cholinergic response in pancreatic islets isolated from overnourished rats. Conclusions: Swimming training avoids obesity development, corrects glucose-induced insulin secretion, as well as, GLP1 insulinotropic response in overnourished rats.